PENGGUNAAN KALIMAT EFEKTIF DALAM KARANGAN DESKRIPSI SISWA KELAS X AP3 SMK NEGERI 1 KOTA JAMBI TAHUN AJARAN 2017/2018 - Fitri Rahmadani; Erlina Zahar; Sujoko Sujoko (Universitas Batanghari, 2018)
The purpose of this research is to describe the use of effective sentence based on the feature of effective sentences in students’ descriptive writing at class X AP3 SMK Negeri 1 Kota Jambi Academic Year 2017/2018. This research is descriptive qualitative. The data is taken from the students writing in a form of sentence in students descriptive writing. Based on the result of the analysis, it can be concluded that there are many mistakes found in using effectve sentence in students descriptive writing at class X AP3 SMK Negeri 1 Kota Jambi Academic Year 2017/2018. From the five effective features of sentence, they are: unity, parallel, stressing in sentence, provident and variation. Based on this result, it is suggested that the students should pay more attention in using effective sentence in writing descriptive text or other texts. Moreover, it is also suggested that the students should pay more attention in making good sentence. Key Words: analysis, effective sentence, descriptive text.